Assessing entrepreneurial and regional‐economic flood impacts on a globalized production facility. Issue 4 (3rd March 2014) - Pfurtscheller, C.; Vetter, M.
Abstract: Indirect economic losses and business interruption effects triggered by natural hazards are widely underestimated by corporate managements. They can exceed direct damages in the case of flood events and are difficult to evaluate because of missing data and methods on a micro‐scale. Existing data can be used for meso‐analysis, but are of little relevance for either mitigation policies or cost‐efficient technical mitigation measures for individual flood‐prone premises. The study represents an interdisciplinary collaboration for improving risk management strategies based on a flood scenario for an individual production company in Austria with high regional‐economic impact. Based on flood modelling, using LiDAR data as source, and on expert judgements, we analyse the entrepreneurial and regional‐economic impacts of a specific production site. The flood model used is based on an HQ100 with a climate change variability of 3%, which is mainly triggered by a change in air temperature and successively increasing heavy rainfall events. The main objective for this assessment is to give result‐based recommendations to improve public and private risk management of the affected area and to provide data for cost–benefit frameworks for technical and nontechnical prevention. Overall, we calculated a total decline of revenues of approximately 14.1 to 14.3 million euros, even though the production site experiences only shallow flooding.